2007
DOI: 10.1089/aid.2007.0132
|View full text |Cite
|
Sign up to set email alerts
|

HIV in the Workplace in Botswana: Incidence, Prevalence, and Disease Severity

Abstract: Few detailed epidemiologic data exist regarding the impact of HIV infection on the workplace in the developing world. In addition, most HIV surveys examine only prevalence, without data on incidence or disease severity. In June 2003, we conducted a voluntary anonymous HIV serosurvey among employees of the Debswana Mining Company, the largest nongovernmental employer in Botswana. Among the 3558 participants, annual HIV incidence was estimated to be 3.4%, and HIV prevalence was 23.8%. HIV-infected participants h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…In this manufacturing company, HIV prevalence appears to be inversely proportionate to employees' job skill level. Similar findings were described in workplace studies by Evian et al (2004), Colvin et al (2007) and Riviello et al (2007). In this set of surveys, lowest HIV prevalence was found in the upper-management category and highest prevalence in the unskilled category.…”
Section: Specific Hiv Prevalence By Job Categorysupporting
confidence: 91%
See 3 more Smart Citations
“…In this manufacturing company, HIV prevalence appears to be inversely proportionate to employees' job skill level. Similar findings were described in workplace studies by Evian et al (2004), Colvin et al (2007) and Riviello et al (2007). In this set of surveys, lowest HIV prevalence was found in the upper-management category and highest prevalence in the unskilled category.…”
Section: Specific Hiv Prevalence By Job Categorysupporting
confidence: 91%
“…For both surveys, HIV prevalence was highest in the 30-39-year-old age group, which has been commonly found for male-dominated workplaces. These patterns are similar to those found in studies by Evian et al (2004), Colvin et al (2007) and Riviello et al (2007). HIV prevalence did not increase for the 18-29-year-old age group, however significant increases occurred in the aged 30-39 and aged 40-49 groups, and possibly also in the age 50+ category.…”
Section: Specific Hiv Prevalence By Age Groupsupporting
confidence: 90%
See 2 more Smart Citations
“…Eventually, the country's economy would suffer dramatically with decreasing figures of growth, consumption and productivity. A 2007 published study on the labour force of Debswana, the diamond public-private partnership, concluded that 'among the 3558 participants [of the survey], annual HIV incidence was estimated to be 3.4 per cent, and HIV prevalence was 23.8 per cent' (Riviello et al, 2007). It would also scare foreign investors away.…”
Section: Botswana's Renewed Struggle For Survivalmentioning
confidence: 99%